2009
DOI: 10.1177/0165025408098020
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between keeping a secret and psychosocial adjustment in adolescence

Abstract: Increasing bodies of evidence suggest that keeping secrets may be detrimental to well-being and adjustment, whereas confiding secrets may alleviate the detriments of secrecy and benefit well-being and adjustment. However, few studies have addressed the consequences of keeping and confiding secrets simultaneously, and even fewer have done so longitudinally. This article reports on a two-wave longitudinal survey study among 278 adolescents (aged 13—18 years) that examined the associations of keeping and confidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
1
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 62 publications
(83 reference statements)
5
62
1
15
Order By: Relevance
“…The parent/peer effects theoretical perspective has received empirical support in a limited number of longitudinal studies. For example, adolescentreported open communication with parents has been found to predict SCC over time across adolescence but not vice versa (Frijns & Finkenauer, 2009;Van Dijk et al, 2014). Moreover, focusing on the intergenerational transmission of SCC, parental SCC has been found to predict adolescents' SCC but not vice versa (Crocetti, Rubini, Branje, Koot, & Meeus, 2016).…”
Section: Parent and Best Friend Relationship Quality And Sccmentioning
confidence: 99%
“…The parent/peer effects theoretical perspective has received empirical support in a limited number of longitudinal studies. For example, adolescentreported open communication with parents has been found to predict SCC over time across adolescence but not vice versa (Frijns & Finkenauer, 2009;Van Dijk et al, 2014). Moreover, focusing on the intergenerational transmission of SCC, parental SCC has been found to predict adolescents' SCC but not vice versa (Crocetti, Rubini, Branje, Koot, & Meeus, 2016).…”
Section: Parent and Best Friend Relationship Quality And Sccmentioning
confidence: 99%
“…Mede om die reden bestaat er onder LHB-jongeren een angst om gepest te worden; daarom proberen zij hun seksuele voorkeur op school vaak geheim te houden (Van Bergen & Spiegel, 2014). Het verborgen houden van hun seksuele voorkeur lijkt echter slecht voor hun geestelijk welbevinden (Frijns & Finkenauer 2009;Van Bergen & Spiegel, 2014) onder meer omdat het gepaard gaat met spanningen om tegen hun wens in door anderen "uit de kast geduwd" te worden (Meyer, 2003). Sommige LHB-jongeren gaan op basis van dergelijke angsten over tot allerlei stressvolle vormen van aanpassing om zo voor heteroseksueel te kunnen doorgaan (Meyer, 2003;Van Bergen & Van Lisdonk, 2010a).…”
Section: Diana Van Bergen En Tali Spiegelunclassified
“…In larger groups, self-disclosure has been identified as a critical component in building cohesion, but the majority of studies have used therapeutic groups as the basis for investigation (Alcoholics Anonymous, 1990;Empey & Rabow, 1961). Meta-analyses have found psychological benefits of self-disclosure, including less distress, negative affect, and depression (Frattaroli, 2006), whereas withholding secrets is associated with poorer psychosocial adjustment and the physical experience of being weighed down (Frijns & Finkenauer, 2009;Slepian et al, 2012). In another meta-analysis of 205 studies, women were found more likely to reveal secrets than men (Dindia & Allen, 1992).…”
Section: Introductionmentioning
confidence: 99%